The Sharing Telecommunication Information Resources Management System Based on B/S model and GIS - Hongren Jiang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In order to reduce the repeated construction between telecom operators and telecom facilities, improve the utilization rate of telecom infrastructure, the use efficiency of earth ,the sources of energy and the consumption of raw materials, the protection of the natural environment and landscape, promote the sharing of telecom infrastructure. With the current telecom information highly integrated conditions, considering the current business models and business processes, establish centralized telecom infrastructure information platform, to strengthen the integration of resources monitoring and performance evaluation. On the analysis of the current situation and existing problems of domestic industry on the basis of this unit, combining with the management requirements, research and design based on B/S model and WebGIS the co-construction and sharing of information management system, this paper first demand analysis in this system, on the basis of the detailed design of the system are presented. The scheme is mainly includes: information release platform, basic information recorded: "base stations, utility, tower, computer room, room points, piping, rod way, transmission lines and stations nets" as the foundation object management, data query and statistics, the economic comparison, assessment rating, log monitoring, telecom infrastructure geographic information system (GIS) and other modules. The business management system will daily management work in network platform, solving day-to-day business management problems. Improve business processing efficiency, to change the current business processing mode, improving the business management level. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4800